A "natural experiment" in cardiovascular epidemiology in the early 21st century. Issue 3 (1st March 2003) - Sekikawa, A; Horiuchi, B Y; Edmundowicz, D; Ueshima, H; Curb, J D; Sutton-Tyrrell, K; Okamura, T; Kadowaki, T; Kashiwagi, A; Mitsunami, K; Murata, K; Nakamura, Y; et al.
Abstract : Despite similar traditional risk factors, morbidity and mortality rates from coronary heart disease in western and non-western cohorts remain substantially different. Careful study of such cohorts may help identify novel risk factors for CHD, and contribute to the formulation of new preventive strategies